Midazolam for treatment of refractory neonatal seizures: a case report - José Luiz Dias Gherpelli; Francisco José C. Luccas; Israel Roitman; Eduardo Juan Troster (Arquivos de Neuro-Psiquiatria)
Midazolam is a short-acting water soluble benzodiazepine that has been used with an increasing frequency in the last years. Although there are reports on its use in status epilepticus, there is none in the neonatal period. A pre-term (35 w) AGA newborn infant with a severe hypoxic-ischemic encephalopathy secondary to grade ED hyaline membrane disease developed status epilepticus in the first 6 hours of life and was successfully treated with midazolam after phenobarbital and phenytoin failed to achieve seizure control. Dosage schedule was 0.2 mg/kg IV, followed by continuous infusion of 0.025 mg/kg/h. Midazolam is an effective drug for neonatal status epilepticus and more experience should accumulate before it can be routinely employed in the neonatal period. This case shows that it is a possible option before using more dangerous drugs, such as thionembutal.